Efeitos do exercício resistido na obesidade: revisão sistemática - SILVA, Rita de Cassia da Fonseca (2023)
Obesity is associated with several complications and has increased the risk of mortality in obese individuals. The practice of physical activity is important for health The change in lifestyle is one of the fundamental interventions to improve these individuals, and the practice of physical exercises is one of its components. Based on this, the aim of this study was to analyze the benefits of resistance training in obese individuals. The methodology used was a systematic review of articles published between 2017 and 2022, in PubMed databases. After the data search, 5 articles were included in the search. The results found prove the effects and benefits that physical exercise brings in obesity. Among the main benefits found we can highlight: Increase in barsal metabolism, and improvement in body composition. The results also point to benefits with aerobic and resistance exercises that reduce weight loss, improve physical fitness, promote an increase in lean mass, improvements in the percentage of fat, lipids, physical, metabolic and cardiorespiratory function.